2016
DOI: 10.1590/0102-6720201600s10009
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Disorders Associated With Helicobacter Pylori in the Roux-en-Y Bypass Gastric Pouch

Abstract: Background: The prevalence of Helicobacter pylori in obese candidates for bariatric surgery and its role in the emergence of inflammatory lesions after surgery has not been well established. Aim: To identify the incidence of inflammatory lesions in the stomach after bariatric surgery and to correlate it with H. pylori infection. Methods: This is a prospective study with 216 patients undergoing Roux-en-Y gastric bypass. These patients underwent histopathological endoscopy to detect H. pylori prior to surgery. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…As for the prevalence of HP infection in the population with obesity, Gonzalez-Heredia et al (19) reported a prevalence of HP in approximately 17% of individuals with obesity, a frequency much lower than the observed in the present study (55%). Chaves et al (20) described HP infection present in 40.7%, a proportion more comparable to that of the present study. Other studies report a highly variable prevalence of HP infection in pre-operative bariatric patients, with data ranging from 6.9 to 61.3% (21,22) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As for the prevalence of HP infection in the population with obesity, Gonzalez-Heredia et al (19) reported a prevalence of HP in approximately 17% of individuals with obesity, a frequency much lower than the observed in the present study (55%). Chaves et al (20) described HP infection present in 40.7%, a proportion more comparable to that of the present study. Other studies report a highly variable prevalence of HP infection in pre-operative bariatric patients, with data ranging from 6.9 to 61.3% (21,22) .…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the HP eradication treatment led to an eradication rate close to 70%, while in the study carried out by Chaves et al (20) , this same scheme was successful in approximately 80%. Csendes et al (29) found HP infection in 46.8% of patients before BS and in 31.6% afterward, even with the eradication therapy pre-operatively.…”
Section: Discussionsupporting
confidence: 39%
“…On the other hand, alterations of the autonomic system leak visceral sensation in obese patients and those explain asymptomatic pathological situations might be misleading. Several studies also found a correlation with H. pylori and extra gastric manifestations [17], also positive in the population of obese and morbidly obese patients pre and post surgery [18] with clinical pathology of idiopathic trombocitopenic purpura, CagA-positive H. pylori infection in iron-deficiency anemia and ischemic heart disease. Data accumulating from epidemic studies are also positive about the correlation to chronic idiopathic urticaria.…”
Section: European Guidelines Following Maastricht Iv/ Florencementioning
confidence: 89%
“…Clearly, the need of tailored H. pylori eradication regimen for candidates of any bariatric surgery is important to reduce the prevalence of postsurgical lesions. The literature report clear evidence of reduced incidence of visceral perforation and marginal ulcer in patients beeing eradicated of H. pylori prior bariatric surgery to non-eradicated group [18,23]. Data also present higher risk persistency even that the H. pylori eradication protocol was performed preoperatively [24] but to clarify the impact and correlation between H. pylori and a type of postoperative complications well-designed RCTs are obligatory.…”
Section: European Guidelines Following Maastricht Iv/ Florencementioning
confidence: 99%